An empirical study of green retrofit technologies and policies for aged residential buildings in Hong Kong. (July 2021) - Tan, Yongtao; Luo, Ting; Xue, Xiaolong; Shen, Geoffrey Qiping; Zhang, Guomin; Hou, Lei
Abstract: Given the ever-increasing number of aged residential buildings in Hong Kong, green retrofit provides a sustainable solution for improving existing aged residential buildings' performance instead of constructing new buildings. Studies on green retrofit technologies (GRTs) and green retrofit policies (GRPs) have received great attention globally. However, few studies have been done to understand the applicability and importance of GRTs and GRPs, and the impacts of GRPs on the application of GRTs in a particular region, such as Hong Kong. Therefore, based on a questionnaire survey conducted in Hong Kong, this study aims to further examine the GRTs and GRPs that have been identified in a previous study. The applicability of the GRTs and the importance of the GRPs for green retrofit of aged residential buildings in Hong Kong were studies, the correlations between the GRTs and GRPs were analyzed, and a priority guide was developed for promoting green retrofit of aged residential buildings in Hong Kong. The findings can help various stakeholders to have a better understanding of the GRTs and provide valuable references for the local government to develop future GRPs. Furthermore, this study also provides a fundamental guide for future green retrofit research and development in the local and global contexts. Highlights: Green retrofit technologies and policies for aged residential buildings in Hong Kong were examined. A questionnaire survey was conducted to collect professionals' viewpoints. The relationships between green retrofit technologies and policies were analyzed. A priority guide was developed for promoting building green retrofit in Hong Kong.